10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
IntroductionGuidelines recommend concomitant surgical ablation for atrial fibrillation (AF) in selected patients with pre-existing AF undergoing coronary artery bypass grafting (CABG). We assessed temporal trends, early clinical outcomes, and factors associated with surgical AF ablation in patients undergoing isolated CABG in the United Kingdom.MethodsRetrospective observational cohort study including all patients with pre-existing AF undergoing first-time, elective or urgent isolated CABG from 2011 to April 2019 using the United Kingdom National Cardiac Surgical Audit database. Temporal trends, in-hospital outcomes, and factors associated with concomitant surgical AF ablation were evaluated.ResultsA total of 5337 patients were included; 747 (14.0%) underwent concomitant surgical AF ablation. The annual ablation rate ranged from 11.2% to 16.3% during the study period. After inverse probability treatment weighting, surgical AF ablation was associated with longer cardiopulmonary bypass time (103 [79, 129] vs 82 [63, 104] minutes, p < 0.0001), aortic cross-clamp time (58 [41, 77] vs 48 [35, 64] minutes, p < 0.0001), and deep sternal wound infection (2.04% vs 0.95%, p = 0.021). There were no differences in the incidence of in-hospital mortality, return to theatre bleeding/tamponade, postoperative stroke, or postoperative dialysis.ConclusionIn UK patients with pre-existing AF undergoing isolated CABG, concomitant surgical AF ablation was used in approximately one in seven cases. It was associated with longer operative times and a higher weighted incidence of deep sternal wound infection, but no statistically significant differences were observed in mortality, stroke, dialysis or return to theatre. Longer-term data are needed to define freedom from atrial tachyarrthymia and stroke, anticoagulation use, and survival.